An Analyzing on Statistical Data Analysis Skill Needs Among Graduates - Mazdan, Ali Amaran; Puteri Ariana, A.Mohd Puat; Mohd Sharizam, Hamzah; Nur Fardilla Nadia, Abu Bakar (Secholian Publication (Kuala Lumpur, Malaysia), 2022)
The skill of analyzing statistical data is a skill that uses quantitative or numerical methods. The need for a systematic research process usually requires a foundation of quantitative skills even if little other than its importance in the realm of future employment and important knowledge for every student, especially for those who conduct research scientifically. Creative arts students are students who venture into the field of arts and creative studies who mostly use qualitative methods in their research. Yet is there a need for systematic statistical data analysis skills in the scope of their study? Therefore, to answer this question, this study examines the need for data analysis skills among creative arts students. A total of 102 sets of questionnaires were distributed to undergraduate students from various programs of the Faculty of Applied and Creative Arts UNIMAS. Descriptive analysis was used to analyze the questionnaire data using Statistical Package for the Social Science (SPSS) version 26.0. Overall finding showed that statistical data analysis skills are very necessary among creative arts students.